Перiодичнi функцiї на замкнених траєкторiях з групою симетрiй L44РС - Плахтiєнко, М.П. (Видавничий дім "Академперіодика" НАН України, 2008)
The multitude of periodic functions, which is determined by the motion of a point on closed
symmetric flat curves of the one-parametric family is constructed. These functions are obtained
by the calculation of Cartesian coordinates of the point as functions of the arc length of a line.
The 2π-periodic functions which differ from classical ones by the sign of curvature at every
point of their existence are discovered.